160. Role of SVMPs, Matrikines and TLR4 in Snake Venom Induced Edema and Inflammation - Fox, Jay W. (2012)
Poster publicado en revista del congreso: 17th World Congress of the International Society on Toxinology & Venom Week 2012, 4th International Scientific Symposium on All Things Venomous